Advance decisions to refuse treatment. (9th May 2019) - Griffith, Richard
Abstract : Richard Griffith, Senior Lecturer in Health Law at Swansea University, considers the case ofNHS Cumbria CCG v Rushton [2018], and the importance of recording and giving effect to advance decisions to refuse treatment